Development and validation of a person-centered abortion scale: the experiences of care in private facilities in Kenya - May Sudhinaraset; Amanda Landrian; Patience A. Afulani; Beth Phillips; Nadia Diamond-Smith; Sun Cotter (BMC, 2020)
Abstract Background There is a need for a standardized way to measure person-centered care for abortion. This study developed and validated a measure of person-centered abortion care. Methods Items for person-centered abortion care were developed from literature reviews, expert review, and cognitive interviews, and administered with 371 women who received a safe abortion service from private health clinics in Nairobi, Kenya. Exploratory factor analyses were performed and stratified by surgical abortion procedures and medication abortion. Bivariate linear regressions assessed for criterion validity. Results We developed a 24-item unifying scale for person-centered abortion care including two sub-scales. The two sub-scales identified were: 1) Respectful and Supportive Care (14 items for medication abortion, 15 items for surgical abortion); and 2) Communication and Autonomy (9 items for both medication and surgical abortion). The person-centered abortion care scale had high content, construct, criterion validity, and reliability. Conclusions This validated scale will facilitate measurement and further research to better understand women's experiences during abortion care and to improve the quality of women's overall reproductive health experiences to improve health outcomes.